Persepsi Konsumen Atas Risiko Pembelian Melalui Media Online - Stephanie Astrid Ayu (BIP's JURNAL BISNIS PERSPEKTIF, 2019)
The purpose of this study is to investigate empirically the risk factors that will influence both simultaneously and partially on the customer's decision to make purchases through online media. This research was used by using questionnaires methods. Population of this study was student and employee at Darma Cendika Catholic University, Surabaya. Research involves to 220 respondent. The sampling technique in this study was used convenience sampling and purposive sampling. The technique of data analysis using factor confirmatory analysis and multiple linier regression analysis. The result of the research by factor analyze confirmatory showed that new factor risk is Psychological Risk. The results of multiple linear regression analysis indicate Privacy Risk, Quality Risk, Purchase Behavior Risk, Information Risk, Product Delivery Risk, Psychological Risk, Health Risk, and Product Size Risk have a significant negative effect on customer Purchasing Decisions through online media.